Enhancement in electrical and thermal performance of high‐temperature vulcanized silicone rubber composites for outdoor insulating applications. Issue 46 (1st June 2020) - Azizi, Sohrab; Momen, Gelareh; Ouellet‐Plamondon, Claudiane; David, Eric
Abstract: High‐temperature vulcanized silicone rubber composites are highly desirable as outdoor insulating materials due to their immense thermal and electrical performance. The aim of this work is to study the role of co‐combined fillers (modified fumed silica [MFS], titanium dioxide [TiO2 ], with graphene [G]) on electrical and thermal properties of silicone rubber (S) composites. The dielectric response of S/MFS_10 phr and S/TiO2 _20 composites tailored with 2 phr G was characterized by broadband dielectric spectroscopy. The hybrid filler/composites were found to show higher thermal stability when 2 phr G was added. In addition, a low quantity of G filler was found to slightly increase the AC dielectric breakdown strength of the S/MFS_10 and S/TiO2 _20, where an improvement of 3 and 5% was found, respectively. Several steps were observed in the thermal decomposition of the S rubber composites by thermogravimetric analysis‐Fourier‐transform infrared spectroscopy. Our findings revealed great potentials for fabricating hybrid‐filler/silicone rubber composites with enhanced electrical and thermal properties for outdoor insulating applications. Abstract :